Impact of Antibiotic Resistance on the Development of Recurrent and Relapsing Symptomatic Urinary Tract Infection in Kidney Recipients. Issue 4 (12th February 2015) - Bodro, M.; Sanclemente, G.; Lipperheide, I.; Allali, M.; Marco, F.; Bosch, J.; Cofan, F.; Ricart, M. J.; Esforzado, N.; Oppenheimer, F.; Moreno, A.; Cervera, C.
Abstract : We sought to determine the frequency, risk factors, and clinical impact of recurrent urinary tract infections (UTI) in kidney transplant recipients. Of 867 patients who received a kidney transplant between 2003 and 2010, 174 (20%) presented at least one episode of UTI. Fifty‐five patients presented a recurrent UTI (32%) and 78% of them could be also considered relapsing episodes. Recurrent UTI was caused by extended‐spectrum betalactamase (ESBL)–producing Klebsiella pneumoniae (31%), followed by non‐ESBL producing Escherichia coli (15%), multidrug‐resistant (MDR) Pseudomonas aeruginosa (14%), and ESBL‐producing E. coli (13%). The variables associated with a higher risk of recurrent UTI were a first or second episode of infection by MDR bacteria (OR 12; 95%CI 528), age >60 years (OR 2.2; 95%CI 1.15.1), and reoperation (OR 3; 95%CI 1.37.1). In addition, more relapses were recorded in patients with UTI caused by MDR organisms than in those with susceptible microorganisms. There were no differences in acute rejection, graft function, graft loss or 1 year mortality between groups. In conclusion, recurrent UTI is frequent among kidney recipients and associated with MDR organism. Classic risk factors for UTI (female gender and diabetes) are absent in kidney recipients, thus highlighting the relevance of uropathogens in this population. Abstract : A study of kidney transplant recipients shows that 20% presented at least one episode of urinary tract infection, of which a third had recurrent infection, with multi‐drug‐resistant bacteria being the most important risk factor for recurrence.